BIOLOGICAL STUDY PROGRAM SCHOOL OF LIFE SCIENCES AND TECHNOLOGY - TRIKOTAMI EFFENDI (NIM : 10614031), MEISSY
Simple arm exercises that are carried out repetitively for a long time can form muscle activity patterns. One of the important problems in repetitive exercises is the onset of muscle fatigue which can cause decrease in muscle capacity to carry out motoric task on ongoing basis. Surface Electromyography (sEMG) is a technique for measuring muscle activity that can be used to detect fatigue in the muscles. Muscle fatigue is indicated by decrease in the frequency of sEMG signal. This study aims to determine the pattern of muscle activity and indication of muscle fatigue in repetitive movements measured through sEMG. In this study three healthy subjects were asked to participate in an arm flexion extension exercise. The exercise consisted of three sessions where each session was 4 minutes long with a 1 minute break between sessions. The sEMG signal was taken in the biceps brachii section and the muscle contraction-relaxation pattern between sessions was analyzed. The mean power frequency (MPF) from the envelope of the initial and the final contraction of each session were analyzed to determine any indication of muscle fatigue. The three subjects showed different muscle activity patterns. Subject 1 showed a muscle contraction-relaxation pattern that was increasingly efficient and accurate, while subject 2 showed a pattern of contraction-relaxation that was faster along with repetition of movement. Conversely, the contraction-relaxation pattern in subject 3 was not well defined throughout the exercise. The analysis results at the beginning and end of the exercise as well as at the beginning and end of each session showed a tendency of decreased MPF value. Based on statistical tests, the decrease in MPF values that occurred at the beginning and end of each session from the three subjects was not significantly different (p> 0.05). The decrease in MPF values that occurred at the beginning and the end of the exercise from subject 1 and 3 were significantly different (p <0.05), but in subject 2 the decrease was not significantly different (p> 0.05). Decreasing MPF values indicates muscle fatigue which can be caused by a decrease in muscle cell sensitivity. From this study, it can be concluded that the pattern of muscle activity of each individual is different and the repetitive exercise of arm flexion extension indicates muscle fatigue.